Epidural Mepivacaine for Cesarean Section: Maternal and Neonatal Effects. Issue 2 (April 1987) - Abboud, Therese K.; Moore, Michael J.; Jacobs, Jerry; Murakawa, Kazushige; Soraya, Manoutchehr; Zhu, Jay
Abstract : The effects of epidural anesthesia using mepivacaine on maternal blood pressure, newborn Apgar scores, neonatal acid-base status, and the Early Neonatal Neurobehavioral Scale (ENNS) were studied in 21 pregnant women undergoing cesarean section. Maternal and neonatal blood levels of mepivacaine were also determined. Neonatal outcome was compared with a control group of 14 neonates of healthy mothers who received 3% 2-chloroprocaine for elective cesarean section. All patients had satisfactory anesthesia for cesarean section with an onset of 19 ± 1.8 minutes (mean ± SEM) and duration of 95 ± 11.9 minutes. Hypotension developed in two patients, and they were treated with intravenous ephedrine. All neonates had Apgar scores of 8 or more at 1 and 5 minutes and normal blood gases and acid-base status. None of the variables of the ENNS differed significantly between the mepivacaine and the chloroprocaine control group with the exception of truncal tone, which was significantly higher in the mepivacaine group ( p < 0.05). Mepivacaine was detected in all maternal and fetal samples, and the umbilical venous to maternal venous ratio was 0.57 ± 0.17 (mean ± SEM).